Pyriform Sinus Fistula in Children: Preferred Imaging Modality and Risk Factors for Diagnostic Delay - Tong Chen; Guijie Ge; Jianglong Chen; Xiuhao Zhao; Qingfeng Sheng; Linlin Zhu; Weijue Xu; Jiangbin Liu; Zhibao Lv (Frontiers Media S.A., 2020)
Background: Diagnostic delay of pyriform sinus fistula (PSF) continues to challenge clinicians, and the preferred imaging modality is yet to be verified. The purpose of this study was to investigate the preferred imaging modality for PSF and the possible risk factors for a longer diagnostic delay.Methods: Medical records of patients with a surgically confirmed PSF from 2014 to 2018 were retrospectively evaluated. A comparison of the first esophagography timing with a true-positive (TP) result and that with a false-negative (FN) result was made. Data of computed tomography (CT) performed immediately after esophagography were also analyzed. In addition, the factors related to diagnostic delay were analyzed using multivariate regression models.Results: A total of 147 patients ranging in age from 0 to 16 years (median: 5.2 years) were included. The mean time since the symptom onset of the first esophagography with TP result was significantly longer than that of the examination with FN result (95.18 ± 79.12 vs. 52.59 ± 42.40 days, P = 0.032). When the time since the symptom onset was less than 12 weeks, the false-negative rate (FNR) of the first esophagography was declining dramatically with a longer time interval. Among 18 cases with an FN result of the first esophagography, the fistulous tract was finally identified in seven cases using an immediate CT. The mean of diagnostic delay was 12.28 months. Besides, rural residency was an independent risk factor for a longer diagnostic delay.Conclusion: Joint examination of esophagography and an immediate CT is the preferred imaging modality for the diagnosis of PSF in children. It is inadvisable to perform the first esophagography when the time since the symptom onset is less than 12 weeks. Besides, the rural residency is an independent risk factor for a longer diagnostic delay.